G534 The use of a whatsapp™ broadcast group to improve knowledge and engagement of adolescents with Type 1 diabetes. (27th April 2016) - Blackstock, S; Solomon, S; Watson, M; Kumar, P
Abstract : Context: We present the development and evaluation of WhatsApp messaging to improve engagement adolescents with Type 1 Diabetes Mellitus at a District General Hospital in West London District. Problem: Adolescence is a particularly challenging time where metabolic control often deteriorates. Many adolescents find diabetes socially isolating. Engagement and compliance are challenging issues and traditional healthcare models don't always seem relevant to this population. This issue was highlighted when a patient was admitted to resus with severe diabetic keto-acidosis who was text-messaging on her mobile phone and disclosed she missed her last clinic appointment. The way patients are accessing health information is changing. Social media is a rapidly expanding and under-utilised resource. Now more people world-wide have access to mobile phones than tooth-brushes. Intervention and assessment of problem: The concept of a WhatsApp broadcast was developed. This virtual community allows information to be disseminated quickly to a large group of patients without individuals feeling singled out. The group allows patients to share information and expertise in self-management, ask questions and form relationships with peers, with the aim of bridging gaps between appointments and improving motivation and self-management. Patients participated in the design process through a co-production session using a graphic facilitator to stimulate strategic dialogue. Co-production is where health-care providers and service users work together to identify problems and solutions to improve their care. The session was attended by 6 patients and 4 staff members. Patients believed this concept would improve patient motivation. Design: All children with type 1 diabetes aged 11 years or greater were invited to participate in the WhatsApp group from March 2015. Twenty patients and 4 staff are now members. Informed consent was obtained from children and parents. Patient safety is maintained as the group is a 'broadcast' rather than an 'open group, ' therefore replies are directed to the diabetic team phone, who have to approve messages sent ensuring quality control. Measurement of improvement and outcomes: Qualitative and quantitative data was collected to assess patient experience. Feedback was overwhelmingly positive. Patients send messages to the group, such as 'snack advice.' They write questions and send pictures for their peers. 'Patient user' sent messages increased from 7 messages in April to 88 messages in August 2015 demonstrating increasing user engagement. Qualitative data was obtained from patients and parents using questionnaires and semi-structured interviews. Recurring themes highlighted on thematic analysis included improved access to information and the benefits of talking to others with diabetes. One mother quoted 'This is what my son needs, he knows no one with diabetes and often feels he is the only one who has to inject then acts out.' A patient quoted 'I find it easier to ask questions on the WhatsApp group [compared to clinic].' All (100%) of survey responders felt that their access to information had improved since joining the WhatsApp group and that they had learnt something new. Sixty seven percent of patients felt more motivated since they joined the group. HbA1c data was also reviewed pre and post intervention. The mean HbA1c changed from 9.7 to 9%. The Median HbA1c changed from 9.8 to 7.9%. There was no change in missed clinic appointment rates, however the two patients who most frequently did not attend clinic were amongst the highest WhatsApp users, one had a significant improvement in HbA1c. This could indicate that this tool could be useful for targeting those who are particularly difficult to engage. Conclusion: Digital strategies can easily be adopted into Diabetes care. This innovative approach highlights the successful use of technology to improve patient engagement and access to information. This model may be particularly useful at targeting those who are difficult to engage (Figure 1 ).